FAKTOR DETERMINAN AKHLAK REMAJA - Suharman Suharman (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2018)
The background of the research concerns with the existence of some phenomenon about teenagers morality decreasing that happen nowadays. It can be shown from the light violation like cheating, ditching, ignoring the prayer, or using clothes that do not cover their bodies, to the heavy violation like drinking alcohol, taking drugs, promiscuity, abortion, or involved in crimes such as brawl, motorcycle gang, robbery or rape. The scope of this study is morals and the factors that influence it. The factors are limited to religiosity factors as internal factors as well as parenting factors, peers, and mass media as external factors. This research data were taken through questionnaire, psychology scale and observation. The data were obtained and analyzed by using the statistical package for social science program (spss) for windows version 20.0. The Techniques that were used to analyze in this study include: descriptive analysis and inferential analysis.